2012
DOI: 10.1590/s1516-35982012000600014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GnRH administration on ovulation and fertility in ewes subjected to estrous synchronization

Abstract: -The objective of this study was to verify the effects of GnRH on ovulation and pregnancy of ewes subjected to a short-term synchronization of estrus. Santa Inês and crossbred Santa Inês/Dorper ewes received 60 mg MAP sponges during 6 days plus 300 IU eCG and 30 μg d-cloprostenol 24 h prior to sponge withdrawal (SW). Ewes were assigned to receive 0.9% NaCl solution (T control ; n = 32) or 25 μg GnRH (licerelin, T GnRH ; n = 34) 24 hours after SW. Each group was assigned to intrauterine insemination by laparosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 49 publications
3
24
1
Order By: Relevance
“…Although a comparison of reproductive variables in the present study to those in previous reports is difficult due to differences in breed, age, nutritional status, and synchronization treatment, our current findings are similar to those reported earlier [10,11]. No ewe from G 24h showed estrous behavior, similar to a previous finding in wool sheep treated with GnRH [12].…”
Section: Discussionsupporting
confidence: 89%
“…Although a comparison of reproductive variables in the present study to those in previous reports is difficult due to differences in breed, age, nutritional status, and synchronization treatment, our current findings are similar to those reported earlier [10,11]. No ewe from G 24h showed estrous behavior, similar to a previous finding in wool sheep treated with GnRH [12].…”
Section: Discussionsupporting
confidence: 89%
“…Santa Inês sheep have a relatively low ovulation rate (1–1.3 ovulation per oestrous‐induced ewe; Cavalcanti, Brandão, Nogueira, & Fonseca, ; Teixeira et al., ; Venturi et al., ) and lamb productivity (1.3 lambs born per ewe; Mexia et al., ). Overall, the average egg/embryo recovery rate of 41.2% (7/17) obtained in this study appeared to be low.…”
Section: Discussionmentioning
confidence: 99%
“…(Beck et al 1996;Bazer et al 1998;Cavalcanti et al 2012;Ataman et al 2013) and cattle (Kaçar et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Lashari and Tasawar (2010) also reported that GnRH injections at the time of mating are effects on synchronization. Another study by Cavalcanti et al (2012) expressed that the injection of 25 μg GnRH 24 h after sponge removal had no significant effect on the time of oestrus. Luther et al (2007) also tested GnRH treatment did not affect the efficiency of oestrus synchronization in ewes during the breeding season (GnRH, 85.1% versus without GnRH, 90.3%).…”
Section: Discussionmentioning
confidence: 99%